(untitled) (Fiep Bulletin - online, 2011)
In the area of health care involves several factors, knowledge and practices which may cause or exacerbate physical and mental suffering, which requires careful interact with the existence of the subject became ill and the networks of relationships between health workers and users. This study examines perceptions of individuals living with HIV / AIDS on the care received at a clinic specializing in HIV / AIDS by identifying and analyzing psychosocial needs before the experiences of professional care. Qualitative research conducted with 34 subjects through semi-structured, analyzed and interpreted through the humanistic approach of existential understanding. The results were collated from two categories: the service as a possible meeting, and perception of professional care. Results show that the service is carried out in a very quickly way by the professionals, which ends up harming the listening and understanding the needs of the users, showing anxieties and existential anguishes. Subjects observe attitudes and expressions of professional involvement, perceived difficulties related to structural failures and organizational service. Emerge needs to reflect the understanding and humanization of the practices.